THE SPECIFICS OF NONCOMPACTED CARDIOMYOPATHY MANIFESTATION - R. P. Myasnikov; O. V. Blagova; O. V. Kulikova; E. A. Mershina; M. S. Kharlap; E. Yu. Andreenko; S. N. Koretsky; S. E. Serdyuk; E. V. Bazaeva; I. A. Virabova; S. A. Beregovskaya; V. E. Sinitsyn; et al. (Кардиоваскулярная терапия и профилактика)
Noncompacted myocardium of the left ventricle (NMLV), or noncompacted cardiomyopathy, according to the World Health Organization classification is a non-classified cardiomyopathy with not fully known origins. This type of cardiomyopathy presents with an increased trabecularity with deep intertrabecular sinuses in the LV. NMLV exists as either isolated or together with other inherited syndromes. Clinical presentation of NMLV varies: there are asymptomatic forms, or those with progression of the disease, with heart failure, angina, thromboembolism, life-threatening ventricular rhythm disorders; in some cases, the disease manifests as sudden cardiac death. At the same time, there is a problem of NMLV decompensation, with significant impact of acute myocarditis comorbidity. The article presents a case of the female patient, whose disease presented with heart failure at the background of acute myocarditis and further onset of everything for NMLV.